Organic and Inorganic Dietary Phosphorus and Its Management in Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2010)
Dietary phosphorus control is often a main strategy in the management of patients with chronic kidney disease. Dietary protein is a major source of phosphorus intake. Recent data indicate that imposed dietary phosphorus restriction may compromise the need for adequate protein intake, leading to protein-energy wasting and possibly to increased mortality. The two main sources of dietary phosphorus are organic, including animal and vegetarian proteins, and inorganic, mostly food preservatives. Animal-based foods and plant are abundant in organic phosphorus. Usually 40% to 60% of animal-based phosphorus is absorbed; this varies by degree of gastrointestinal vitamin-D-receptor activation, whereas plant phosphorus, mostly associated with phytates, is less absorbable by human gastrointestinal tract. Up to 100% of inorganic phosphorus in processed foods may be absorbed; ie, phosphorus in processed cheese and some soda (cola) drinks. A recent study suggests that a higher dietary phosphorus-protein intake ratio is associated with incremental death risk in patients on long-term hemodialysis. Hence, for phosphorus management in chronic kidney disease, in addition to absolute dietary phosphorus content, the chemical structure (inorganic versus organic), type (animal versus plant), and phosphorus-protein ratio should be considered. We recommend foods and supplements with no or lowest quantity of inorganic phosphorus additives, more plant-based proteins, and a dietary phosphorus-protein ratio of less than 10 mg/g. Fresh (nonprocessed) egg white (phosphorus-protein ratio less than 2 mg/g) is a good example of desirable food, which contains a high proportion of essential amino acids with low amounts of fat, cholesterol, and phosphorus.